Peningkatan Kemampuan Motorik Halus Anak Usia 5-6 Tahun melalui Kolase Bahan Bekas di TK Dahlia Polongaan - Paillin, Sarah Langi; Ulfah, St. Maria (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to improve the fine motor skills of 5-6 year old children at Dahlia Polongaan Kindergarten through collage activities using recycled materials. The background of this study is the challenge in learning fine motor skills, which often leads to boredom and fatigue with repetitive coloring and pasting activities. The subjects were 12 children in grade B1 of Kindergarten. This study was conducted in two cycles, each consisting of two meetings, using the Kemmis and McTaggart spiral model. Data were collected through observation and analyzed qualitatively using a percentage formula. The results showed a significant increase in children's fine motor skills. In Cycle I, the average achievement was 69.66%, with the criteria of Developing According to Expectations (BSH). After the revision of the method and implementation of Cycle II, the average achievement increased to 82.14%, with the criteria of Developing Very Well (BSB). This proves that using collage with recycled materials is effective in improving children's fine motor skills and overcoming learning boredom.